Seasonal variability of the East Greenland Coastal Current. Issue 6 (25th June 2014) - Bacon, Sheldon; Marshall, Abigail; Holliday, N. Penny; Aksenov, Yevgeny; Dye, Stephen R.
Abstract The East Greenland Coastal Current (EGCC) is characterized as cold, low‐salinity polar waters flowing equatorward on the east Greenland shelf. It is an important conduit of freshwater from the Arctic Ocean, but our present understanding of it is poor, outside of an assortment of measurements which stem mainly from summertime visits by research vessels. This manuscript first describes measurements from moored instruments deployed on the East Greenland shelf (∼63°N) between 2000 and 2004. The measurements are then used to show that a high‐resolution coupled ice‐ocean global general circulation model supports a realistic representation of the EGCC. The results show that the EGCC exists throughout the year and is stronger in winter than in summer. The model EGCC seawater transports are a maximum (minimum) in February (August), at 3.8 (1.9) × 106 m3 s−1. Freshwater transports, including modeled estimates of sea ice transport and referenced to salinity 35.0, are a maximum (minimum) in February (August) at 106 (59) × 103 m3 s−1. The model results show that wind and buoyancy forcing are of similar importance to EGCC transport. An empirical decomposition of the buoyancy‐forced transport into a buoyancy‐only component and a coupled wind and buoyancy component indicates the two to be of similar magnitude in winter. The model annual mean freshwater flux of ∼80–90 × 103 m3 s−1 approaches 50% of the net rate of Arctic freshwater gain, underlining the climatic importance of the EGCC.